2018
DOI: 10.1111/lcrp.12142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating treatment outcomes for young people participating in a high‐intensity therapeutic violence intervention in the English Youth Custody Service

Abstract: Purpose A specialized unit for long‐term sentenced male young people sought to provide additional support to those convicted of the gravest violent offences, who had the highest risk of further offending. One key element was the introduction of a violence reduction intervention, Life Minus Violence‐Enhanced (LMV‐E). The present study evaluated LMV‐E. Methods Participants (N = 21, starting age = 16–17 years) were convicted of a violent offence and had a history of custodial and or community violence. Pre‐ and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
2
0
3
Order By: Relevance
“…Another British study found that training detention center staff in motivational interviewing principles, particularly focusing on emotion management and interpersonal style, led to improvements in empathy and propensity to violence measured by psychological tests and self report (Derbyshire et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another British study found that training detention center staff in motivational interviewing principles, particularly focusing on emotion management and interpersonal style, led to improvements in empathy and propensity to violence measured by psychological tests and self report (Derbyshire et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…S obzirom da ova populacija najčešće biva sudski smeštena u korektivnu instituciju, ostaje dovoljno vrememena za procenu rizika za recidiv, planiranje, primenu i evaluaciju efekata primenjenih programa. Jedan od takvih programa je i Life Minus Violence-Enhanced (LMV-E) za mlade nasilnike osuđene na dugovremene kazne (Derbyshire et al, 2019). Studija koju je sprovela ova grupa autora (2019) imala je za cilj procenu efektivnosti LMV-E programa.…”
Section: Programi Usmereni Na Mlade Nasilnike U Korektivno-rehabilitacionom Ambijentuunclassified
“…Praćenje je pokazalo povoljne stope agresije unutar zajednice i u instituciji. Autori studije (Derbyshire et al, 2019) iznose zaključke da je smanjenje rizika nasilja važno i ukazuju na opšte smanjenje rizika od agresije nakon ove intervencije. Značajno je da su učesnici takođe pokazali poboljšanje empatije, kao jednog od direktnih ciljeva tretmana.…”
Section: Programi Usmereni Na Mlade Nasilnike U Korektivno-rehabilitacionom Ambijentuunclassified
See 1 more Smart Citation
“…Empathy role-plays are undertaken in the consequences for self and others module and provide an opportunity for group members to take on roles of victims affected by their aggression. The LMV-E programme has been implemented in secure forensic hospitals with male and female patients, in a young offender establishment, and with high risk, women offenders in prison (Daffern et al , 2018; Derbyshire et al , 2019).…”
Section: The Life Minus Violence-enhanced (Lmv-e) Programmementioning
confidence: 99%